Insights into peptide nucleic acid (PNA) structural features: The crystal structure of a d-lysine-based chiral PNA–DNA duplex - Menchise, Valeria (National Academy of Sciences, 2003)
Peptide nucleic acids (PNAs) are oligonucleotide analogues in which the sugar-phosphate backbone has been replaced by a pseudopeptide skeleton. They bind DNA and RNA with high specificity and selectivity, leading to PNA–RNA and PNA–DNA hybrids more stable than the corresponding nucleic acid complexes. The binding affinity and selectivity of PNAs for nucleic acids can be modified by the introduction of stereogenic centers (such as d-Lys-based units) into the PNA backbone. To investigate the structural features of chiral PNAs, the structure of a PNA decamer containing three d-Lys-based monomers (namely H-GpnTpnApnGpnAdlTdlCdlApnCpnTpn-NH(2), in which pn represents a pseudopeptide link and dl represents a d-Lys analogue) hybridized with its complementary antiparallel DNA has been solved at a 1.66-Å resolution by means of a single-wavelength anomalous diffraction experiment on a brominated derivative. Thed-Lys-based chiral PNA–DNA (LPD) heteroduplex adopts the so-called P-helix conformation. From the substantial similarity between the PNA conformation in LPD and the conformations observed in other PNA structures, it can be concluded that PNAs possess intrinsic conformational preferences for the P-helix, and that their flexibility is rather restricted. The conformational rigidity of PNAs is enhanced by the presence of the chiral centers, limiting the ability of PNA strands to adopt other conformations and, ultimately, increasing the selectivity in molecular recognition.